THE INNOVATION POTENTIAL OF THE EARTH SCIENCES IN THE HIGHER GEOGRAPHICAL AND ENVIRONMENTAL EDUCATION - Черванёв, И. Г.; Боков, В. А. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2016)
Training at geographical departments in universities begins with a course on "Earth science". Its object of study is a holistic self-organizing natural system – landscape geosphere, which is the global environment of human society. In the formation of ideas about the landscape geosphere a large contribution was made by B. Varenius, A. Humboldt, K. Ritter, P. I. Brounov, A. N. Krasnov, V. I. Vernadsky, A. A. Grigoriev. Modern understanding of earth sciences, as the science of landscape geosphere, is associated with S. V. Kalesnik (40-50-ies of XX century).A new stage in the development of Geosciences began in the 70-ies, when the use of space vehicles, research vessels and polar stations intensified the study of the Earth's surface, especially oceans and polar regions.The main task of the earth science is to give a holistic view of the shell surface of the globe on the basis of modern ideas of self-organization of the earth's systems. The training course includes the following topics: 1.Sources of knowledge and methods of the Geosciences. 2. The Earth in Space. 3. The composition and structure of the landscape geosphere. 4. Dynamics of the landscape sphere. 5. Development of the landscape sphere. 6. People in a landscape geosphere. 7 Global change. Earth science and noosphere’s development.The course focuses on respect for earth's nature, demonstrates the dangers of careless destruction of delicate mechanisms of geosystem connections. In some respects, the Earth science discharges the functions of natural philosophy, laying in the minds of students skills of  understanding the nature of the earth's surface as an integral part of the evolving Cosmos. The course fulfills the philosophical, natural-scientific and socio-humanistic functions:- philosophical: Earth is our common home — is a complex self-organizing system, established and functioning according to its own laws; violation of these laws is fraught with the destruction of the system;- natural science: the revelation of the totality interactions of physical, chemical, biological and geological processes, their integration with the processes of formation and functioning of human society, a description of the processes of integration objects, diverse in space - time and substance and energy characteristics;- socio-humanistic: to contribute through knowledge of the basic regularities of structure and functioning of the landscape sphere to preserve and improve the living conditions of mankind.Earth science serves as methodological basis of component courses: geomorphology, climatology and meteorology, hydrology, oceanography, soil science, biogeography.It gives the possibility to consider these subjects, first, from the point of view of understanding close interactions of all parts of the earth's surface, secondly, understanding of geosystems as self-developing sites where insufficient use of simple causal relations need analysis of circular interactions with positive and negative feedbacks. This, in turn, poses a challenge to improving geographical and environmental education through the development of mathematical apparatus of synergetics. Training course leads geographers to use mathematical modeling and GIS technologies, understanding the laws of self-organization of the earth's systems.